Pengaruh Pengungkapan Tata Kelola Perusahaan dan Board Gender Terhadap Imbal Hasil Saham - Zahrotunisa Laeliyah; Aloysius Harry Mukti (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
The purpose of this study is to determine the Disclosure of Corporate Governance and Board Gender on Stock Returns. The data in this study uses secondary data obtained from published annual reports and websites, namely finance.yahoo.com. The approach taken in this study is a quantitative approach with the sampling method in this study is purposive sampling, namely sampling using certain criteria and obtained as many as 73 data samples. The analytical method used is Multiple Linear Regression. The results of this study indicate that Corporate Governance Disclosure has no effect on Stock Returns, while the Gender Board has a positive effect on Stock Returns.